2017
DOI: 10.1080/15384101.2017.1284714
|View full text |Cite
|
Sign up to set email alerts
|

Myogenic potential of human alveolar mucosa derived cells

Abstract: Difficulties related to the obtainment of stem/progenitor cells from skeletal muscle tissue make the search for new sources of myogenic cells highly relevant. Alveolar mucosa might be considered as a perspective candidate due to availability and high proliferative capacity of its cells. Human alveolar mucosa cells (AMC) were obtained from gingival biopsy samples collected from 10 healthy donors and cultured up to 10 passages. AMC matched the generally accepted multipotent mesenchymal stromal cells criteria and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The biocompatibility of the fibrous mats was analyzed using human mesenchymal stromal cells (MSCs) isolated from gingival mucosa, as described in [ 25 ]. The MSC cultural media consisted of Dulbecco’s Modified Eagle’s Medium (DMEM)/F12 (1:1, Biolot, St. Petersburg, Russia) supplemented with 10% fetal calf serum (HyClone, Logan, UT, USA), l-glutamine (5 mg/mL, Gibco, Gaithersburg, MD, USA), insulin–transferrin–sodium selenite (1:100, Biolot, St. Petersburg, Russia), bFGF (20 ng/mL, ProSpec, Rehovot, Israel), and gentamycin (50 μg/mL, Paneco, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…The biocompatibility of the fibrous mats was analyzed using human mesenchymal stromal cells (MSCs) isolated from gingival mucosa, as described in [ 25 ]. The MSC cultural media consisted of Dulbecco’s Modified Eagle’s Medium (DMEM)/F12 (1:1, Biolot, St. Petersburg, Russia) supplemented with 10% fetal calf serum (HyClone, Logan, UT, USA), l-glutamine (5 mg/mL, Gibco, Gaithersburg, MD, USA), insulin–transferrin–sodium selenite (1:100, Biolot, St. Petersburg, Russia), bFGF (20 ng/mL, ProSpec, Rehovot, Israel), and gentamycin (50 μg/mL, Paneco, Moscow, Russia).…”
Section: Methodsmentioning
confidence: 99%
“…ABMSCs are found to have sufficiently high proliferative capacity and myogenic potential. ABMSCs are positive expressions of CD29, CD44, CD73, CD90, CD105, CD146, and STRO-1, and negative for CD11b, CD19, CD31, CD34, CD45, and CD324 (Table 1) [107][108][109][110]. Protein arrays were used to identify the contents of ABMSCs and found that ABMSCs expressed IL-6 and MCP-1.…”
Section: Alveolar Bone-derived Mesenchymal Stem Cellsmentioning
confidence: 99%
“…The biocompatibility and cytotoxicity tests were performed using the primary culture of mesenchymal stromal cells (MSCs) isolated from human gingival mucosa as described in [85]. The cells were cultivated in the medium that contained Dulbecco's Modified Eagle's Medium (DMEM)/F12 (1:1, Biolot, St. Petersburg, Russia), 10% fetal calf serum (HyClone, Logan, UT, USA), L-glutamine (5 mg/mL, Gibco, Gaithersburg, MD, USA), insulin-transferrin-sodium selenite (1:100, Biolot, St. Petersburg, Russia), bFGF (20 ng/mL, ProSpec, Rehovot, Israel), and gentamycin (50 µg/mL, Paneco, Moscow, Russia).…”
Section: In Vitro Cytotoxicity Assaysmentioning
confidence: 99%